Chlorogenic Acids Profile of Coffee arabica By-Products (Cascara and Silverskin): A Comparison with Green and Roasted Beans - Marlene Machado; Susana Machado; Helena Ferreira; Maria Beatriz P. P. Oliveira; Rita C. Alves (Biology and Life Sciences Forum, 2022)
Coffee, one of the most traded commodities in the world, contains compounds with health-promoting properties [...]